PELAKSANAAN PELATIHAN BERBASIS KEBUTUHAN DI BERBAGAI NEGARA: META SINTESIS KOMPONEN PELATIHAN - Eko Eko Sulistiono; Rembulan Catra Banyu Biru (Universitas Cenderawasih, 2020)
This research was conducted to synthesize the process of implementing training based on needs which is limited to the identification process, the learning process, and the evaluation process. The study was conducted using the meta-synthesis method on seven manuscripts of research results on farmer training in several countries. The results of the synthesis show that (1) the need-based training needs identification process is carried out directly to the training participants, either by survey or oral interview, (2) training participants are also involved in designing the learning process, (3) in several countries evaluation is carried out before the training is carried out (pre-test) and after the training is completed (post-test), then using a survey to find out the extent of the participants' abilities, however, there is also an evaluation that is only carried out after the training is done by observing changes experienced by the training participants. The implications of these findings can be used as a reference for other trainings wishing to adopt the identification process, the learning process, and the evaluation process from several other countries.Keywords: needs-based training; identification of needs; learning process; evaluation process